MULTIPOLARITY OF TEACHER EDUCATION IN THE WORLD COMMUNITY - R. M. Medetova (Galaxy International Interdisciplinary Research Journal, 2023)
This article deals with the multidimensional development of teacher education in the modern world. Emphasis is placed on the creation of a multipolar unified educational space.